Implementation Strategies for Digital Teaching Materials Utilizing Gamification to Enhance Student Learning Motivation: A Systematic Literature Review - Nayumi Warta Nabila; Khalila Humairo Ramadhani; Bq. Roswin Tiarti Sari; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2026)
ABSTRACT The development of digital technology has driven innovation in creating more interactive and engaging learning materials for students. This study aims to analyze the implementation strategy for gamification-based digital learning materials to increase student learning motivation, drawing on a review of scientific literature. The method used is a systematic literature study by reviewing research articles published between 2022 and 2025 from various national and international journals relevant to the topic of gamification in education. A total of 15 journal articles were analyzed using content analysis techniques to identify implementation patterns, types of platforms used, and their impact on student learning motivation. The results of the study indicate that the application of gamification in digital learning materials, such as the use of points, levels, badges, leaderboards, and interactive challenges, has been proven to increase learning motivation, student engagement, and a more enjoyable learning experience. In addition, the integration of gamification through various digital platforms such as Quizizz, Kahoot, Wordwall, and Learning Management System (LMS)-based learning applications has a positive influence on active student participation in the learning process. However, the effectiveness of gamification implementation is greatly influenced by learning design, teacher readiness to utilize technology, and the availability of digital infrastructure. Therefore, strategies for implementing gamification-based digital teaching materials need to be systematically designed to support more interactive, innovative learning and be oriented towards increasing student motivation in the digital era.